(untitled) (Patan Pragya, 2025)
Inclusion, also known as affirmative action, has been regarded as one of the tools to increase the participation of underrepresented groups and communities in public services. However, many scholars believe that this system needs proper oversight, as it may undermine the merit-based system in the civil service. In Nepal, the past merit-based bureaucratic system failed to recruit people from marginalized communities in proportion to their numbers. Due to this, a social imbalance was created, and it prevented a larger section of society from having access to opportunities and thereby excluded them. Similarly, the absence of respectable representation in nation-building activities prevented equal benefit sharing. To minimize the imbalance in public service, the Civil Service Act (2007) of Nepal introduced a reservation system in government jobs. Similarly, the government has implemented a social inclusion policy in politics, government appointments, the budget, and other policy making process in various agencies. This article, based on the secondary source of data, aims to evaluate the effectiveness of the inclusion policy in the civil service, educational institutions, policies, and other various sectors of Nepal.